STUDENTS’ DIFFICULTIES IN MEMORIZING ENGLISH VOCABULARY - Zalsabilla, Fira Rizky Suciana; Jefry, Riny; Amin, Fatimah Hidayahni (Universitas Negeri Makassar, 2025)
This research aims to explore the difficulties of Business English Communication students in memorizing English vocabulary and explore the strategies used to overcome these difficulties. Vocabulary mastery is essential for language proficiency, yet students often struggle due to several factors. The research objectives include identifying key challenges and exploring effective strategies students use to overcome them. This research uses a descriptive qualitative method with interview and observation data collection techniques, collecting data focused on the meaning and subjective experiences of 4th-semester Business English students in the process of memorizing English vocabulary by involving 6 students. The results show that students have difficulty in memorizing vocabulary in 8 factors: Mispronunciation, Misspelling, The Length of Vocabulary, Multiple Meanings Cause Confusion, Difficult Recognition in Similar Words, Lack of Identifying While Listening, Unfamiliar Words, and Misunderstanding in Catching Non-verbal Cues While Speaking. Despite these obstacles, students utilize strategies such as repetitive practice, contextual learning, and digital tools to enhance vocabulary retention. Conclusions indicate that while students employ effective strategies, long-term retention remains a challenge without consistent practice. Recommendations include providing more practice opportunities, emphasizing phonetics in learning, integrating vocabulary into real-life contexts, and encouraging the use of technology for self-directed learning. These approaches can significantly improve students' vocabulary acquisition and overall language proficiency.